2015
DOI: 10.1073/pnas.1414894112
|View full text |Cite
|
Sign up to set email alerts
|

Recent shifts in the occurrence, cause, and magnitude of animal mass mortality events

Abstract: Mass mortality events (MMEs) are rapidly occurring catastrophic demographic events that punctuate background mortality levels. Individual MMEs are staggering in their observed magnitude: removing more than 90% of a population, resulting in the death of more than a billion individuals, or producing 700 million tons of dead biomass in a single event. Despite extensive documentation of individual MMEs, we have no understanding of the major features characterizing the occurrence and magnitude of MMEs, their causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
265
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(283 citation statements)
references
References 32 publications
2
265
0
4
Order By: Relevance
“…For example, the normally benign bacteria Pasteurella hamolytica, which can be precipitated by stress, has been linked to catastrophic mass-mortality events in the critically endangered saiga antelope (Saiga tatarica) following severe winters (Bekenov et al 1998). Recent modelling of data from over 720 animal mass-mortality events in over 2400 populations has indicated that mortality events associated with concurrent stressors and disease have increased in frequency from the 1940s to 2000s (Fey et al 2015). The imperative to investigate the relationship between stress and disease in wildlife is greater now than ever.…”
Section: (1) Climate Changementioning
confidence: 99%
“…For example, the normally benign bacteria Pasteurella hamolytica, which can be precipitated by stress, has been linked to catastrophic mass-mortality events in the critically endangered saiga antelope (Saiga tatarica) following severe winters (Bekenov et al 1998). Recent modelling of data from over 720 animal mass-mortality events in over 2400 populations has indicated that mortality events associated with concurrent stressors and disease have increased in frequency from the 1940s to 2000s (Fey et al 2015). The imperative to investigate the relationship between stress and disease in wildlife is greater now than ever.…”
Section: (1) Climate Changementioning
confidence: 99%
“…Mass mortality events (hereafter MMEs) represent demographic catastrophes that can affect simultaneously all life stages (Lande, 1993). Recently the magnitudes of MMEs are changing among animal taxa, with increases for birds, marine invertebrates, and fishes (Fey et al, 2015). Analyzing the impact of these events at appropriate scales (spatial and temporal) and biological organization levels (species, populations, communities) is crucial to accurately anticipate future changes in marine ecosystems and propose adapted management and conservation plans (Pairaud et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Animal infectious diseases are a cause for losses to biodiversity [1] and a risk to human health due to 28 zoonosis [2][3][4]. Infectious diseases that threaten livestock can also lead to economic damages and 29 contribute to persistent poverty [5][6][7].…”
mentioning
confidence: 99%